Anticancer Potential of Mefenamic Acid Derivatives with Platelet-Derived Growth Factor Inhibitory Property - Patel, Snehal S.; Tripathi, Richa; Chavda, Vishal K.; Savjani, Jignasa K. (Anti-Cancer Agents in Medicinal Chemistry, 2020)
Background: Numerous studies suggest that non-steroidal anti-inflammatory drugs reduce cancer cell proliferation, progression, angiogenesis, apoptosis, and invasiveness. Objective: The current study focuses on the evaluation of novel mefenamic acid derivatives for the treatment of hepatocellular carcinoma. Methods: Derivatives were subjected to molecular modeling for prediction of pharmacological activity using software, followed by synthesis and in vitro assay. In in vivo study, disease was induced with N-Nitrosodiethylamine followed by 2-acetylaminofluorene orally for 2 weeks. After 12 weeks of induction, treatment was given for a period of one week. At the end of the treatment, determination of liver weight, a number of nodules, biochemical parameters, immunohistochemistry, histopathology, and gene expression studies, were carried out. Results: Based on molecular docking score for PDGF-α (Platelet-Derived Growth Factor) and IC50 values in HepG2 cell line study, JS-PFA was selected for the in vivo study where JS-PFA showed a statistically significant reduction in a number of nodules and liver weight. Protective role of JS-PFA has been observed in tumorspecific markers like α-fetoprotein, carcinoembryonic antigen, and lactate dehydrogenase levels. The JS-PFA has shown a significant reduction in PDGF-α levels as well as liver markers and total bilirubin levels. Histopathological analysis also showed a protective effect. The results of immunohistochemical analysis of P53 and down-regulation of vascular endothelial growth factor and matrix metalloproteinases-9 genes suggest that derivative inhibits PDGF mediated tumor growth and leads to apoptosis, inhibition of angiogenesis, and metastasis. Conclusion: The effectiveness of JS-PFA in our studies suggests targeting PDGF by COX 2 inhibitor can serve as a novel treatment strategy for the treatment of HCC.
Keywords: Anticarcinogenic agents